Screening of native isolates of Trichoderma spp. of Jammu for their biocontrol potential through hydrolytic enzyme activities - MONI GUPTA and DEEPIKA SHARMA, SACHIN GUPTA*, SURUCHI MAHAJAN (Indian Phytopathology, 2016)
Trichoderma spp. are well described biocontrol fungi for its lytic activity and antagonistic properties against phytopathogens. The present studies were conducted to biochemically characterize Trichoderma spp. isolated from soils of Jammu. A total of fifty native isolates of Trichoderma spp. were screened on the basis of their antifungal activity using dual culture technique. Twenty promising isolates were evaluated for the secretion of extracellular hydrolytic enzymes viz. cellulases, chitinases and Î²-1, 3-glucanases. Enzyme activity detected in agar plates using their respective inducers as sole carbon sources and further tests for enzyme production in broth culture revealed that the majority of the isolates showed maximum specific enzyme activity up to 6th day of incubation with few exceptions were FL322, OR26X and OR27 for cellulase; BR1, FL21 and CE32 for chitinase and 1CR2, AG20, FL41, FL322 and OR26X for glucanase which showed regular increasing trend up to 9 days. However, maximum cellulase activity was detected in AG52 (3.957 U/mg protein) followed by FL60 (3.151 U/mg protein). Highest chitinase activity was observed in AG52 (3.458 U/mg protein) followed by VE56 (2.728 U/mg protein) and glucanase activity was highest in VE56 (2.995 U/mg protein) followed by AG52 (2.642 U/mg protein) and FL60 (2.538 U/mg protein). SDS-PAGE profiling of the protein precipitate from culture filtrate exhibited remarkable variability. A total of forty bands ranging the size from 14.3 kDa to 97 kDa were detected in the isolates.